A study of public’s perception about the factors that lead to the increment of child abuse in central Malacca - Borhanudin, Izat Marlina; Mohd Isa, Rodzilawati (2008)
Child abuse is a serious problem. Nowadays, Malaysia is faced with this critical problem. Everyday we hear new cases that included children such as kidnapping, rapes, murder and violence. The main purpose of this study is to find what factors lead to an increment of child abuse in Central Malacca. A random sample of 100 people in central Malacca was used. The findings showed several factors that lead to increment in child abuse cases.